Evaluation and Identification of Stable Chickpea Lines for Yield-Contributing Traits from an Association Mapping Panel - Philanim Wungmarong Shimray; C. Bharadwaj; B. S. Patil; S. Mukesh Sankar; Neeraj Kumar; Sneha Priya Pappula Reddy; Tripti Singhal; Venkatraman Hegde; Swarup K. Parida; Manish Roorkiwal; Rajeev K. Varshney; Preeti Verma (Agronomy, 2022)
An association mapping panel consisting of 380 genotypes of chickpea was evaluated for three different years, including 2014–2015, 2015–2016 and 2016–2017, for yield-contributing parameters, including the seed number and seed weight. The AMMI analysis presented mainly concentrated on the seed weight and seed number, which are the two most important yield-contributing traits. The genotypes contributed 93.08% of the total variance, while the interaction effect was comparatively low, with 4.1% for the two traits. AMMI biplot analysis identified IG5986, IG5982, ILC6025 and ICCV14307 as desirable genotypes for the seed weight and IG5893, ILC6891 and IG5856 for the seed number. Identifying stable genotypes would help in strategic planning for yield improvement through component trait breeding.